Orientalist Studies on the Authenticity of Prophetic Hadiths: A Phase Analysis of Western Scepticism - Rahman, Ryan Arief; Widodo, Chandra Dwisetyo; Hidayat, Muhammad Sofian (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
This article focuses on analyzing Orientalist arguments against hadith in the phase of Western skepticism. In this study, hadith is the subject and the main basis of discussion. The progress of Islamic civilization in the past has been an attraction for orientalists in studying Islam to subjugate Islamic civilization. This made hadith one of the targets of the orientalists' studies since it is one of the sources of Islamic epistemology. The skepticism of the early generation of orientalists claimed that hadith is a collection of anecdotes. This description will be explained using the library research method, focusing on the argumentation of orientalists in the phase of Western skepticism. The author analyses the data using content analysis. The author finds that there is a misunderstanding in the argumentation of the early generation of orientalists, and the argumentation is weak in terms of methodological and historical truth.